The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/jbmr.2295
|View full text |Cite
|
Sign up to set email alerts
|

SH3BP2 Cherubism Mutation Potentiates TNF-α–Induced Osteoclastogenesis via NFATc1 and TNF-α–Mediated Inflammatory Bone Loss

Abstract: Cherubism (OMIM#118400) is a genetic disorder with excessive jawbone resorption caused by mutations in the signaling adaptor protein SH3BP2. Studies on the mouse model for cherubism carrying a P416R knock-in mutation have revealed that mutant SH3BP2 enhances TNF-α production and RANKL-induced osteoclast differentiation in myeloid cells. TNF-α is expressed in human cherubism lesions, which contain a large number of TRAP-positive multinucleated cells, and TNF-α plays a critical role in inflammatory bone destruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
97
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(103 citation statements)
references
References 76 publications
(215 reference statements)
5
97
1
Order By: Relevance
“…Gain‐of‐function mutations in SH3BP2 are responsible for a human craniofacial disorder, cherubism (OMIM#118400) . Analysis of a knock‐in mouse model for cherubism revealed that a cherubism mutation increases osteoclastogenesis induced by RANKL and TNF‐α and enhances macrophage responsiveness to pathogen‐associated molecular patterns (PAMPs) via TLRs . SYK is critically required for the increased activation of osteoclasts and macrophages carrying cherubism mutations .…”
Section: Introductionmentioning
confidence: 99%
“…Gain‐of‐function mutations in SH3BP2 are responsible for a human craniofacial disorder, cherubism (OMIM#118400) . Analysis of a knock‐in mouse model for cherubism revealed that a cherubism mutation increases osteoclastogenesis induced by RANKL and TNF‐α and enhances macrophage responsiveness to pathogen‐associated molecular patterns (PAMPs) via TLRs . SYK is critically required for the increased activation of osteoclasts and macrophages carrying cherubism mutations .…”
Section: Introductionmentioning
confidence: 99%
“…SH3BP2 lies within a region that is frequently deleted in individuals with Wolf–Hirschhorn syndrome (Lietman et al., ; Reichenberger et al., ) and previous reports showed that haploinsufficiency does not result in cherubism or cherubism‐like characteristics, suggesting that the mutations in SH3BP2 would lead to a gain of function or would act in a dominant‐negative manner (Miah et al., ; Mukai et al., ). A subsequent study demonstrated that knock‐in mice for SH3BP2 would alter bone quality, reduce osteoblast function, and contribute to bone resorption (Wang et al., ), demonstrating the importance of this gene in the osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BMT was effective even in treating fully inflamed Sh3bp2 KI/KI mice, which were not ameliorated with anti-TNF-α therapy in mice and humans [20, 21], suggesting that wild-type BMT also corrected inflammatory cytokine levels other than TNF-α. We have previously reported that cherubism is a hematopoietic disorder of myeloid lineage cells caused by hyperactive macrophages and osteoclasts [3, 18, 22, 52]. Therefore, we assume that replacement of the mutant macrophages and osteoclasts with those carrying wild-type SH3BP2 is a main cause of the improved symptoms in Sh3bp2 KI/KI mice, which resulted in the comprehensive reconstitution of the expression profile of inflammatory cytokines and osteoclast-mediated bone resorption activity in Sh3bp2 KI/KI recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic deletion of TNF-α in Sh3bp2 KI/KI mice shows a significant rescue of inflammation, suggesting that TNF-α plays a key role in the pathogenesis of inflammation in Sh3bp2 KI/KI mice. In fact, TNF-α is expressed in both multinucleated giant cells and stromal cells in human cherubism lesions [21, 22]. These results led us to investigate whether postnatal administration of anti-TNF-α drug is able to prevent or ameliorate the symptoms in Sh3bp2 KI/KI mice, which is more relevant to clinical cases of human cherubism.…”
Section: Introductionmentioning
confidence: 99%